The revolutionary self social change and the emergence of the modern individual, 1770-1800 - Hunt, Lynn 1945- (W.W. Norton & Company, 2025)
"The eighteenth century was a time of cultural friction: individuals began to assert greater independence and there was a new emphasis on social equality. In this surprising history, Lynn Hunt examines women's expanding societal roles, such as using tea to facilitate conversation between the sexes in Britain. In France, women also pushed boundaries by becoming artists, and printmakers' satiric takes on the elite gave the lower classes a chance to laugh at the upper classes and imagine the potential of political upheaval. Hunt also explores how promotion in French revolutionary armies was based on men's singular capabilities, rather than noble blood, and how the invention of financial instruments such as life insurance and national debt related to a changing idea of national identity. Wide-ranging and thought-provoking, The Revolutionary Self is a fascinating exploration of the conflict between individualism and the group ties that continues to shape our lives today."
Keywords: France / History / Revolution, 1789-1799 / Social aspects; Great Britain / History / 18th century / Social aspects; Individualism / History / 18th century / Social aspects; Women / Social conditions / 18th century; Equality / 18th century; Social change; Grande-Bretagne / Histoire / 18e siècle / Aspect social; Femmes / Conditions sociales / 18e siècle